EFEKTIFITAS GAME POWERPOINT DALAM MENGEMBANGKAN KEMAMPUAN MATEMATIKA PERMULAAN DI TK ASYOFA PADANG - Jhoni Warmansyah (Ta'dib, 2019)
This study aims at determining the effectiveness of powerpoint games in developing initial mathematical abilities. The approach used was quantitative with a quasi experimental method type pretest-posttest group design. The population of this study was all of the group B early young learners in Koto Tangah Subdistrict, Padang City 2018/2019 academic year. The sampling technique used was simple random sampling with a total sample of 30 children. The data were collected by using an initial mathematical ability test adopted from REMA the Research Based Early Mathematics Assessment. Data analysis technique was an independent t-test, seeing a comparison of differences in average scores. The result shows that powerpoint games were effective in developing early mathematical abilities in the experimental group compared to the control group. The use of powerpoint games can be an alternative learning media in developing other aspects of development.